Whole-genome sequencing of a novel Meyerozyma sp. nov, fungi Isolated from Harumanis Mango, Mangifera indica L. in Malaysia - Muhammad Ikhmal, Rosali; Siti Munirah, Musa; Siti Khadijah, Kiram; Yi, Jasmine Teoh Wen; Wei, Siew Shing; Hajar Fauzan, Ahmad (Elsevier, 2025)
The study of plant-associated microbiomes, including fruit microbiomes, has been extensively explored. However, the limitations of traditional phenotypic assessments using microscopy and biochemical tests have highlighted the need for more comprehensive methods for microbe identification. Advancement in high-throughput sequencing technologies helped to shift the focus toward molecular approaches, providing comprehensive analysis on their roles in impacting the environment. In this study, a fungal species was isolated from decayed Harumanis mangoes, and its whole genome was sequenced using the Illumina NovaSeq 6000 platform with short-read protocols. Species identification through BLASTN and phylogenetic tree analysis was performed and confirmed the isolate’s close similarity to Meyerozyma caribbica. Genome assembly revealed a total genome size of Meyerozyma sp. K_B strain was 10,404,240 bp, with GC content of 47.2 %, and 95.4 % completeness based on BUSCO assessment. Gene prediction, and functional annotation revealed a total of 5515 coding genes and 5777 coding sequence regions were predicted, associated with various metabolism pathways particularly carbohydrates biosynthesis such as GH5, GH6, GH7, GH16 and GH18, adaptability in host environment such as stress response and membrane transport, and also secondary metabolite biosynthesis like terpene and NRPS clusters highlighting their diverse function particularly in biocontrol activity. These findings provide valuable genomic insight into the potential of Meyerozyma sp. as a postharvest biocontrol agent for fruit management.